The Magic Porridge Pot - David Pace (Ladybird Books Ltd)
Suitable for children ready to attempt reading, this book retells The Magic Porridge Pot in a simple way using a number of frequently repeated words. The sentences are closely supported by pictures and the story begins with a detailed scene introducing the main characters and vocabulary.